Malnutrition Affects the Urban-Poor Disproportionately: A Study of Nigerian Urban Children of Different Socio-Economic Statuses - Chukwunonso E.C.C. Ejike (MDPI AG, 2016)
Income inequality within the same place of residence may impact the nutritional status of children. This study therefore investigated the impact of income inequality on the nutritional status of children living in the same place of residence, using anthropometric tools. Children in four schools (Schools 1-4) within the vicinity of a housing estate in Umuahia, Nigeria, that charge fees making them 'very affordable', 'affordable', 'expensive' and 'very expensive', respectively, were recruited for the study. Thinness, overweight and obesity were defined using the Cole et al. reference standards. Thinness was present in 10.4% (13.0% of boys, 7.6% of girls); 20.4% (15.6% of boys, 27.3% of girls; and 0.7% (1.4% of boys, 0.0% of girls) of children in Schools 1-3, respectively; but absent in school 4. Only 3.7% (1.4% of boys, 6.1% of girls) and 5.6% (6.3% of boys, 4.5% of girls) of children in Schools 1 and 2, respectively, were overweight/obese. Conversely, 25.8% (18.9% of boys, 32.5% of girls) and 41.6% (38.8% of boys, 45.3% of girls) of children in Schools 3 and 4, respectively, were overweight/obese. The urban-poor (School 2) are clearly affected by malnutrition disproportionately.